Evaluation Of Posyandu Cadres In The Use Of Online Posyandu Information System - Susi Susilawati (Lambung Mangkurat University, 2023)
The Online Posyandu Information System website provides tools for compiling and recording data related to toddlers. The comprehensive data collected from Posyandu activities serves the purpose of monitoring maternal and child health development and disseminating health information. This study evaluates the effectiveness of empowering Posyandu cadres in using the Online Posyandu Information System website. This study is a quantitative research using survey method with a cross-sectional approach. Sampling was carried out using the accidental sampling technique, resulting in a sample size of 56 respondents. The reliability of the questionnaire was assessed using Cronbach's Alpha. Data analysis was carried out using Chi-Square test. Variables examined included age, education, occupation, service period as a cadre, knowledge, use of the Online Posyandu Information System website, infrastructure, and skills. A significant relationship was found between age factors and the use of the Online Posyandu Information System website (P-value <0.0001). Specifically, 46% of Posyandu cadres aged 23-38 years were able to use the website effectively. Furthermore, a significant relationship was found between knowledge level factors and the use of the Online Posyandu Information System website (P-value 0.011). Specifically, 63.4% of Posyandu cadres demonstrated good knowledge in using the website. However, no significant relationship was found between facilities and infrastructure factors and the use of the Online Posyandu Information System website (P-value 0.730). Additionally, a relationship between age and knowledge level factors and the use of the Online Posyandu Information System website was also found. Enhancing Posyandu cadres' capacity is proposed as a strategy to strengthen the use of the Online Posyandu Information System website and improve monitoring and evaluation activities.